¿Cómo amplió el origen de la herbivoría en los tetrápodos las redes tróficas? (Zubía. Revista de ciencias, 2024)
Herbivory is key in trophic webs, but it took a while for it to appear in tetrapods. Comparing the dental geometry of the taxa from Linton, USA, fossil site in which the first amniote capable of consuming plants appeared, we show that vegetables could have been more involved in their diets than what was previously thought. Our results indicate that insectivory is the preceding step to omnivory, based on the similar dentitions and sizes of the taxa with these diets, in addition to the availability of insects and plants.They also show the stability of this ecosystem and the fact that omnivory allowed the appearance of bigger predators, as well as suggesting an important role for the competition between different taxa. This study indicates that the ecosystem of Linton was more similar to the modern ones than it was previously thought.
Keywords: Array; Array; Array; Array